(untitled) (Research, Society and Development, 2022)
This article describes the epidemiological profile of patients hospitalized at a Reference Hospital for Infectious Diseases affected by SARS-CoV-2. This is an observational, descriptive cross-sectional study carried out from secondary data obtained from the Hospital Center for Epidemiological Surveillance of a Reference Hospital in Infectious Diseases in the State of Goiás. Inclusion criteria were patients hospitalized at the institution in 2020 with a detectable PCR diagnosis of SARS-CoV-2. It was observed that 78.8% of the patients were brown, 47.4% of the patients were hospitalized for up to 7 days, 50.4% of the total were female and the age group from 61 to 70 years old accounted for 27.7% of the total. The highest number of deaths was in the age group of 61 to 70 years in both sexes. Patients hospitalized in wards, in an intensive care unit (ICU) and those who died had mostly the same comorbidities: systemic arterial hypertension, diabetes, immunosuppression and heart disease. Patients hospitalized in wards had a lower number of comorbidities than patients hospitalized in the ICU. The number of deaths was higher among patients who had two or more comorbidities. Patients over 60 years of age had a lower chance of cure, demonstrating that the Federal Government’s decision to prioritize this group in the “National Plan for the Operationalization of Vaccination against COVID-19” was assertive, as was the subsequent inclusion of people with comorbidities, since the number of comorbidities is directly related to a lower chance of cure.